Melita mirzajanii n. sp. (Crustacea: Amphipoda: Melitidae), a puzzling new member of the Caspian fauna - Krapp-Schickel, Traudl; Sket, Boris (Zootaxa, 2015)
Described is Melita mirzajanii n. sp. (Melitidae) from the southwestern corner of the Caspian Sea. It shows no particular similarity to any species known from the Mediterranean Sea. It inhabits, as the only amphipod species, dense growths of Amphibalanus cf. improvisus (Darwin 1854) in a port, at low and highly fluctuating salinities. Its most striking characters are: absence of any pleonal or urosomal dorsal teeth (projections), elongated distal article of the mandibular palp, hind margin of last pereopod bases strongly narrowed distad, and epimera posterodistally rectangular. An identification key for the species group of Melita without dorsal teeth and without article 2 on the exopodite of the third uropod is provided.